2019
DOI: 10.3892/mmr.2019.10174
|View full text |Cite
|
Sign up to set email alerts
|

miR‑148 family members are putative biomarkers for sepsis

Abstract: Sepsis is a type of systemic inflammatory response caused by infection. The present study aimed to identify novel targets for the treatment of sepsis. We conducted bioinformatic analysis of the microarray Gene Expression Omnibus dataset GSE12624, which includes data on 34 patients with sepsis and 36 healthy individuals without sepsis. Differentially expressed genes (DEGs) in sepsis patients were identified using Bayesian methods included in the limma package in R. Correlations among the expression values of DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Zboromyrska et al [ 18 ] studied multiplex real-time polymerase chain reaction, the Magicplex TM Sepsis test, the specificity of which was up to 95%, while the sensitivity was only 29%. Dong et al [ 19 ] found that members of the miR-148 family (miR-148A/B and miR-152) were candidate biomarkers for sepsis by studying the Gene Expression Omnibus dataset GSE12624, but further study is required to evaluate the diagnostic performance. Guo et al [ 20 ] found that the AUC value of miR-495 in the diagnosis of sepsis was 0.915 when the cutoff value was 0.655, the sensitivity was 89.5%, and the specificity was 83.0%.…”
Section: Discussionmentioning
confidence: 99%
“…Zboromyrska et al [ 18 ] studied multiplex real-time polymerase chain reaction, the Magicplex TM Sepsis test, the specificity of which was up to 95%, while the sensitivity was only 29%. Dong et al [ 19 ] found that members of the miR-148 family (miR-148A/B and miR-152) were candidate biomarkers for sepsis by studying the Gene Expression Omnibus dataset GSE12624, but further study is required to evaluate the diagnostic performance. Guo et al [ 20 ] found that the AUC value of miR-495 in the diagnosis of sepsis was 0.915 when the cutoff value was 0.655, the sensitivity was 89.5%, and the specificity was 83.0%.…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA has also been used to analyze correlation patterns in sepsis. These research efforts focused on inflammatory cells in vitro ( 21 ), long non-coding RNA ( 22 ), transcription factors and miRNA ( 23 ) based on samples with or without sepsis, but did not distinguish between patients with positive outcomes from those with negative outcomes. A recent study identified two transcription factors, CEBPB and ETV6, associated with mortality outcome via WGCNA ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rather than relating thousands of genes to a clinical trait, WGCNA focuses on the relationship between a few modules and the trait ( Zhang & Horvath, 2005 ; Horvath et al, 2006 ). Recently, WGCNA has been used to explore co-expression patterns in cancer, ischaemic stroke and sepsis ( Dong et al, 2019 ; Niemira et al, 2019 ; Wang et al, 2020 ; Zhang et al, 2020 ). Thus, in this study, we characterized the proteomic profile in patients with sepsis and identified protein co-expression modules by using WGCNA that could be used in the diagnosis of sepsis.…”
Section: Introductionmentioning
confidence: 99%